PENERAPAN MODEL COOPERATIVE TIPE MAKE A MATCH DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS III SD NEGERI 74 PANYIWI MATERI AYO BELAJAR SURAH AL-KAUTSAR - kamal, st ibrah mustafa; Usman, Usman; Nurdianawati, Sri (JRPD (Jurnal Riset Pendidikan Dasar), 2024)
The objectives of this research are 1) To determine the learning process activities in PAdBP in class III at SDN 74 Panyiwi before using the Coopertif model with the make a match method; 2) To find out the implementation of cooperative learning in PAI lessons in class III at SDN 74 Panyiwi; 3) To find out the application of the cooperative learning model in increasing students' learning motivation on the Let's Learn QS material. Al-Kautsar in class III at SDN 74 Panyiwi. This research is a type of classroom action research. The approach used in this research is a qualitative research approach supported by quantitative data. The subjects of this research were 8 class III students consisting of 7 female students and 1 male student. The data collection techniques are observation and questionnaires, while the data analysis techniques used are qualitative analysis techniques through observation sheet data and questionnaire data analysis. The results of this research are 1) Students' learning motivation in PAI lessons on the Let's Learn QS material. Al-Kautsar in class III at SD Negeri 74 Panyiwi is in the very good category with a percentage of student learning motivation observations in cycle I of 67% and at the end of cycle II of 87%; 2) Cooperative learning using the make a match type in PAI lessons on Let's Learn QS.Al-Kautsar material in class III of SD Negeri 74 Panyiwi experienced an increase, namely in cycle I by 67% and cycle II with a percentage of 87%; and 3) Application of the make a match type cooperative learning model can increase students' learning motivation on the Let's Learn QS material. Al-Kautsar in class III at SD Negeri 74 Panyiwi with a percentage in cycle I of 67% while in cycle II the percentage was 87%.Abstract English version written using Calisto MT – 10.  Abstract contain research aim/purposes, methods, and result; written in 1 paragraph, single space.